World cinema through global genres - Costanzo, William V (Chichester, West Sussex, UK : Wiley-Blackwell, 2014)
'World Cinema th75056215rough Global Genres introduces the complex forces of global filmmaking using the popular concept of film genre. The cluster-based organization allows students to acquire a clear understanding of core issues that apply to all films around the world'--
Includes bibliographical references and index.
Keywords: Motion pictures -- Study and teaching; Film genres